PENGEMBANGAN ELEARNING MENGGUNAKAN MOODLE DI SMK MUHAMMADIYAH 2 MUNTILAN - Muhammad Sholeh; Suraya . (JURNAL GAUNG INFORMATIKA, 2017)
The world of education today can not be released with the development of information and communication technology (ICT). Students as protégé with smartphone devices have so easy to access information through internet. This development should be followed by the school's policy of the teachers in optimizing ICT as a medium in the learning process. Through the internet, both teachers and students can complement the learning materials by looking for teaching materials. The Internet can be used to interact between teachers and students as a supporter of the learning process. One means of facilities that can be used is elearning. By using this elearning, both teachers and students can interact with each other outside the classroom. Teachers can upload teaching materials in elearning and students can download teacher materials, as well as in tasks, teachers can optimize elearning as a medium for collecting tasks or working on problems. In the socialization of community service activities conducted in SMK Muhammadiyah 2 Muntilan, developed elearning facilities using Moodle and given training how the teachers can use elearning as one of the media in the learning process and create teaching materials using ICT.